Amyloid duration and entorhinal tau interact to influence cognition in preclinical Alzheimer's disease. (20th December 2022) - Cody, Karly Alex; Koscik, Rebecca Langhough; Jonaitis, Erin M.; Hermann, Bruce P; Chin, Nathaniel A.; Asthana, Sanjay; Christian, Bradley T; Betthauser, Tobey J; Johnson, Sterling C.
Abstract: Background: The degree of involvement of amyloid and tau on cognitive decline in the pre‐symptomatic phase of AD remains unresolved. This study examines whether duration of amyloid positivity and entorhinal tau individually contribute or interact to influence longitudinal cognitive decline in initially unimpaired older individuals. Method: Data were from 358 initially unimpaired individuals from the Wisconsin Registry for Alzheimer's Prevention and Wisconsin Alzheimer's Disease Research Center who underwent amyloid and tau PET imaging and longitudinal cognitive assessment (Baseline age: 59.7 ±6.7 years; 67% female; follow‐up years, Median(IQR)=8.0 (6.1‐9.8); Table 1). Amyloid burden was quantified from cortical 11 C‐PiB DVR, and amyloid duration, quantified as years from PiB positivity (A+/‐; global PiB DVR1.16), was estimated using a sampled iterative local approximation algorithm. Tau burden was quantified using 18 F‐MK‐6240 standard uptake value ratios (SUVRs; 70‐90min, inferior cerebellar grey matter reference region). Linear mixed effects (LME) models (random intercept and age‐related slope; unstructured covariance) investigated contributions of amyloid duration (at MK‐6240 scan) and entorhinal cortex (EC) MK‐6240 uptake to retrospective cognitive decline represented by a modified three‐test Preclinical Alzheimer's Cognitive Composite (PACC‐3). Result: Among initially unimpaired individuals, faster PACC‐3 decline was associated with both longer amyloid duration and higher EC tau. LME models showed significant linear and non‐linear interactions of amyloid duration and EC tau on cognitive decline, suggesting a synergistic effect whereby amyloid duration together with a higher tau burden increases the likelihood of cognitive decline beyond their separable effects (Table 2). To further characterize these interactions, we compared cognitive trajectories of groups based on amyloid duration and EC tau positivity (Figure 1A‐C). Post‐hoc analyses revealed significantly greater decline in the group with 10+ years of amyloid duration and high EC tau compared with all other groups over the study duration (Figure 1C). Conclusion: These results suggest that in this pre‐symptomatic sample, amyloid duration and EC tau were not redundant contributors to decline, but rather interacted to influence decline during the retrospective period of observation. Prospective follow‐up and mediation analyses will be essential to fully elucidate the influence of amyloid duration and early tau on cognitive decline in preclinical Alzheimer's disease.